Zero-expansion glass substrate based on oriented crystal growth and preparation method thereof

By introducing directionally grown quartz crystals into alkali-free glass substrates, the negative expansion characteristics are used to offset the positive expansion characteristics of the glass substrate, the thermal expansion problem of glass materials is solved, and a high-precision and long-life zero-expanded glass substrate is prepared.

CN120364945APending Publication Date: 2025-07-25SICHUAN SHUWANG CHENSHENG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510574567.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The existing glass materials have shortcomings in thermal expansion performance, resulting in deformation and reliability problems of high-precision equipment, and traditional methods are difficult to effectively control crystal orientation and alkali metal-containing influence on glass performance.

Method used

Directional crystal growth technology is adopted to introduce quartzite crystals into alkali-free glass substrates to grow in a directional direction along the c-axis, and the negative expansion characteristics of quartzite crystals are used to cancel each other out, and the crystal growth direction is accurately controlled by combining the melt texture method or floating zone method to prepare a zero-expanded glass substrate.

Benefits of technology

The zero expansion characteristics of the glass substrate in the range of 20-300°C are achieved, which improves the accuracy and life of the equipment, while maintaining good mechanical, optical and electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005388142550000071
    Figure BDA0005388142550000071
  • Figure BDA0005388142550000081
    Figure BDA0005388142550000081
  • Figure BDA0005388142550000091
    Figure BDA0005388142550000091
Patent Text Reader

Abstract

The invention discloses a zero-expansion glass substrate based on oriented crystal growth and a preparation method thereof, and belongs to the technical field of glass. According to the technical scheme, the quartz stone glass comprises an alkali-free glass matrix and quartz stone crystals directionally growing along the c-axis, wherein the content of the quartz stone crystals is 10-30 wt.%; wherein the alkali-free glass matrix is prepared from the following components in percentage by mass: 60 to 70 percent of SiO2, 10 to 18 percent of Al2O3, 5 to 10 percent of B2O3, 1 to 3 percent of MgO, 1 to 3 percent of CaO, 0.5 to 2 percent of TiO2, 0.5 to 2 percent of ZrO2, 1 to 2 percent of SnO2, 1.5 to 3 percent of Ga2O3 and 0.8 to 1.5 percent of Tb4O7. By counteracting the c-axis negative expansion of the quartz crystal and the positive expansion of the glass matrix, the macroscopic zero-expansion characteristic is realized, the thermal expansion problem of equipment is solved, the precision is improved, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass, and particularly to a zero-expansion glass substrate based on directional crystal growth and a preparation method thereof. Background Art

[0002] In the field of modern technology, many high-precision devices and instruments have strict requirements for the thermal expansion properties of the materials used. For example, in precision optical instruments such as optical telescopes and lithography machines, the thermal expansion of the glass substrate will cause deformation of the optical elements, thereby affecting the imaging quality and accuracy; in the packaging of high-power electronic devices, thermal expansion mismatch may cause cracking of the packaging structure, reducing the reliability and service life of the device.

[0003] Due to the disorder of the atomic structure of traditional glass materials, obvious thermal expansion phenomena will occur when the temperature changes, and the thermal expansion coefficient is usually between 5×10 -6 / °C - 10×10 -6 / °C. In order to reduce the thermal expansion coefficient of glass, the existing technologies mainly adopt two methods: one is to add low-expansion or negative-expansion crystal phases to the glass, but these crystal phases are often difficult to be evenly dispersed, and the orientations of the crystals are random, so that the negative-expansion characteristics cannot be fully utilized; the other is to adjust the chemical composition of the glass, however, the effect of this method is limited, and it may have an adverse impact on other properties of the glass such as mechanical strength and optical properties. In addition, some glass formulas used in the existing technologies contain alkali metals, and alkali metal ions are easy to migrate at high temperatures, which will affect the electrical properties and chemical stability of the glass, and may also interfere with the growth of crystals.

[0004] Therefore, it is of great practical significance to develop a zero-expansion glass substrate that can effectively control the crystal orientation, make full use of the negative-expansion characteristics of the crystals, and does not contain alkali metals. Summary of the Invention

[0005] The technical problem to be solved by the present invention is: to overcome the deficiencies of the existing technology, and provide a zero-expansion glass substrate based on directional crystal growth and a preparation method thereof. Through the directional crystal growth technology, the quartz crystals are precisely controlled to grow along a specific crystal direction, and the macroscopic zero expansion is realized by using its anisotropic expansion characteristics. At the same time, a glass formula without alkali metals is adopted to ensure the electrical properties and chemical stability of the alkali-free glass substrate.

[0006] The technical solution of the present invention is as follows:

[0007] On the one hand, the present invention provides a zero-expansion glass substrate based on directional crystal growth, comprising an alkali-free glass matrix and quartz crystals grown in the c-axis direction, with the quartz crystal content being 10-30 wt.%; wherein the alkali-free glass matrix comprises the following components in mass percentages: SiO2: 60-70%, Al2O3: 10-18%, B2O3: 5-10%, MgO: 1-3%, CaO: 1-3%, TiO2: 0.5-2%, ZrO2: 0.5-2%, SnO2: 1-2%, Ga2O3: 1.5-3%, Tb4O7: 0.8-1.5%.

[0008] SiO2: As the main glass network former, it endows the glass with good chemical stability and mechanical strength.

[0009] Al2O3: It can enhance the structural stability of the glass, improve the devitrification resistance and chemical durability of the glass.

[0010] B2O3: It can reduce the melting temperature of the glass, improve the thermal stability and optical properties of the glass.

[0011] MgO: An appropriate amount of MgO can adjust the density and thermal expansion coefficient of the glass, and at the same time improve the mechanical strength of the glass.

[0012] CaO: It helps to reduce the high-temperature viscosity of the glass, and promotes the clarification and homogenization of the glass.

[0013] TiO2: It can increase the refractive index and chemical stability of the glass.

[0014] ZrO2: It can enhance the mechanical strength and wear resistance of the glass.

[0015] SnO2: A clarifying agent, which decomposes at high temperature to produce oxygen, can effectively discharge the bubbles in the glass melt, and improve the transparency and quality of the glass.

[0016] Ga2O3: It can optimize the structure of the glass melt and reduce the interfacial energy of the melt: By the adsorption of Ga 3+ ions at the crystal growth interface to reduce the interfacial energy, so that when the quartz crystal grows, the growth resistance in the c-axis direction is reduced, and it is easier to extend along this direction.

[0017] Tb4O7: It affects the energy distribution at the crystal growth interface, promotes the preferential arrangement of atoms in the c-axis direction during the crystal growth process, thereby enhancing the growth trend of the quartz crystal along the c-axis direction, and cooperating with the growth characteristics of the quartz crystal itself to improve the effect of its directional growth (Tb in Tb4O7 3+Ions have a special 4f electron structure, which can form a local electric field at the crystal growth interface. Through the action of Coulomb force, it guides the orderly arrangement of silicon-oxygen tetrahedrons along the c-axis direction, inhibits the growth in the a- and b-axis directions, and thus enhances the directional growth trend in the c-axis direction.

[0018] The entire alkali-free glass matrix formulation does not contain alkali metal oxides (such as Na2O, K2O, etc.), avoiding the adverse effects of alkali metal ions on crystal growth and glass properties.

[0019] Quartz crystal has anisotropic expansion characteristics. Its a-axis and b-axis directions show positive expansion when the temperature rises, while the c-axis direction shows negative expansion within a certain temperature range. This is because in the structure of quartz crystal, silicon-oxygen tetrahedrons form a helical chain structure by sharing oxygen atoms. In the c-axis direction, when the temperature rises, the distance between the helical chains will decrease, resulting in the negative expansion phenomenon.

[0020] Among them, the quartz crystal grows directionally along the c-axis direction, and its c-axis direction has the characteristic of negative expansion. By offsetting with the positive expansion characteristic of the alkali-free glass matrix, a zero-expansion effect of the glass substrate is achieved macroscopically.

[0021] On the other hand, the present invention provides a method for preparing the above zero-expansion glass substrate based on directional crystal growth, including the following steps:

[0022] S1 Raw material preparation: Mix the components of the alkali-free glass matrix evenly;

[0023] S2 Adding quartz crystal: Introduce quartz crystal into the alkali-free glass matrix by the floating zone method or the melt texture method and control the growth of the quartz crystal along the c-axis direction;

[0024] S3 Annealing: Anneal the alkali-free glass substrate obtained in step S2 to obtain the zero-expansion glass substrate based on directional crystal growth.

[0025] The present invention uses the floating zone method or the melt texture method to control the growth of quartz crystal along the c-axis direction. In the melt texture method, by introducing a seed crystal with a specific orientation into the glass melt and establishing a suitable temperature gradient in the melt, the crystal continues to grow along the orientation of the seed crystal (i.e., the c-axis direction) during the growth process. In the floating zone method, radio frequency heating is used to locally melt the rod-shaped raw material to form a molten zone. By controlling the moving speed and temperature gradient of the molten zone and combining with the orientation of the seed crystal, the quartz crystal is guided to grow along the c-axis direction. By precisely controlling the growth direction and growth speed of the crystal, the quartz crystal can form an orderly arrangement in the glass matrix, thus fully exerting its c-axis negative expansion characteristic and offsetting the positive expansion of the glass matrix to achieve macroscopic zero expansion.

[0026] Preferably, in step S1, the components are mixed by ball milling, and the particle size is < 100 μm.

[0027] Preferably, in step S2, the floating zone method includes the following steps:

[0028] (1) Preparation of the glass melt: Put the components of the non-alkali glass matrix mixed in step S1 into a crucible, place it in a high-temperature furnace, heat it to 1500 - 1700 °C, and keep it warm for 2 - 4 h to melt and clarify the raw materials to form a glass melt;

[0029] (2) Introduction of the seed crystal: Select a quartz seed crystal oriented along the c-axis direction, and insert it into the glass melt at an angle of 85 - 90° with the surface of the glass melt;

[0030] (3) Establishment of the temperature gradient: Establish a temperature gradient of 50 - 100 °C / cm along the c-axis direction of the quartz seed crystal in the glass melt, and the temperature at the end inserted into the glass melt is lower than that at the other end to guide the crystal to grow along the c-axis direction of the seed crystal. When establishing the temperature gradient, it can be achieved by setting different heating zones in the high-temperature furnace, and the temperature is monitored in real time by a thermocouple to ensure the stability of the temperature gradient.

[0031] Preferably, in step (2), the depth of the quartz seed crystal inserted into the glass melt is 1 / 3 - 1 / 2 of the length of the quartz seed crystal.

[0032] Preferably, in step (3), the crystal growth rate is 0.1 - 1 mm / h, so that the quartz crystal gradually grows along the c-axis direction in the glass melt; during the growth process, the temperature gradient and the growth rate should be kept stable to avoid defects in the crystal growth process.

[0033] Preferably, in step S2, the floating zone method includes the following steps:

[0034] 1) Preparation of the rod-shaped blank: Make the components of the non-alkali glass matrix mixed in step S1 into a rod-shaped blank with a diameter of 10 - 30 mm and a length of 100 - 300 mm; then pre-sinter it in a high-temperature furnace, and the pre-sintering temperature is 1000 - 1200 °C, and keep it warm for 1 - 2 h;

[0035] 2) Installation of the seed crystal: Install the quartz seed crystal oriented along the c-axis direction at one end of the floating zone furnace, axially align and coincide with the axis of one end of the rod-shaped blank (the axial deviation between the two is controlled within ±0.1 mm to ensure the precise docking of the seed crystal and the rod-shaped blank and create good conditions for the directional growth of the crystal);

[0036] 3) Radio frequency heating and melt zone formation: Heat one end of the rod-shaped blank to locally melt it and form a melt zone. At the same time, superimpose a mechanical oscillation of 0.1 - 0.5 Hz to promote the uniform distribution of solutes, control the melt zone temperature at 1600 - 1800 °C, and the melt zone length at 5 - 10 mm;

[0037] 4) Establishment of temperature gradient: Establish a temperature gradient of 100 - 200 °C / cm in the direction consistent with the c-axis of the seed crystal in the melt zone. The temperature at the end of the melt zone close to the quartz seed crystal is lower than that at the end far from the quartz seed crystal. When establishing the temperature gradient, use the temperature control system of the floating zone furnace to achieve a stable temperature gradient by adjusting the heating power and cooling rate.

[0038] Preferably, in step 4), the relative moving speed of the rod-shaped blank and the quartz seed crystal is 0.5 - 2 mm / h.

[0039] Preferably, in step S3, after crystal growth is completed, cool the alkali-free glass substrate to 600 - 700 °C, hold for 2 - 6 h, and then cool to room temperature at a rate of 1 - 5 °C / h to eliminate the residual stress inside the glass substrate.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. The alkali-free glass substrate of the present invention has zero expansion characteristics: Utilize the negative expansion of the c-axis of the quartz crystal to offset the positive expansion of the glass matrix, and the thermal expansion coefficient ≤ 0.4×10 -6 / °C in the range of 20 - 300 °C, achieving zero expansion characteristics macroscopically, solving the problem of equipment thermal expansion, and improving accuracy and service life.

[0042] 2. The present invention can precisely control crystal growth: Adopt the melt texture method or the floating zone method, and precisely control the directional growth of the quartz crystal along the c-axis through the seed crystal, temperature gradient, etc., giving full play to the negative expansion characteristics, which is superior to the traditional crystal dispersion method.

[0043] 3. The alkali-free glass substrate prepared by the present invention has excellent comprehensive performance: The alkali-free glass matrix formula enables the glass substrate to have a flexural strength ≥ 310 MPa, with good mechanical properties and the ability to withstand a certain external force without cracking; in the visible light band of 400 - 800 nm, the light transmittance ≥ 90%, meeting the requirements of optical applications; chemical stability: It has good stability in acid chemical media, and the mass loss rate ≤ 0.08% after soaking in 1 mol / L HCl solution for 24 h; good electrical insulation performance: The volume resistivity ≥ 1.1×10 13 Ω·cm, with good electrical insulation performance, meeting the requirements of multiple fields. Specific embodiments

[0044] To enable those skilled in the art to better understand the technical solutions in the present invention, the following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments of the present invention.

[0045] Example 1

[0046] The zero-expansion glass substrate based on directional crystal growth in this embodiment includes an alkali-free glass matrix and quartz crystals grown along the c-axis, and the content of quartz crystals is 20 wt.%. Among them, the alkali-free glass matrix includes the following components in mass percentages: SiO2: 65%, Al2O3: 16.5%, B2O3: 8%, MgO: 2%, CaO: 2%, TiO2: 1%, ZrO2: 1%, SnO2: 1.5%, Ga2O3: 2%, Tb4O7: 1%.

[0047] The preparation method of the zero-expansion glass substrate based on directional crystal growth in this embodiment includes the following steps:

[0048] S1 Raw material preparation: Weigh each component with a purity ≥ 99.5 wt.%, and ball-mill and mix them until the particle size < 50 μm;

[0049] S2 Adding quartz crystals: Introduce quartz crystals into the alkali-free glass matrix by the floating zone method and control the growth of quartz crystals along the c-axis direction. Specifically, it includes the following steps:

[0050] (1) Preparation of glass melt: Put the components of the alkali-free glass matrix mixed in step S1 into a high-temperature resistant platinum crucible, place it in a high-temperature furnace, heat it to 1600 °C, and keep it warm for 3 h to melt and clarify the raw materials to form a glass melt; during the melting process, the melt can be appropriately stirred to promote the homogenization of components;

[0051] (2) Introduction of seed crystal: Select a quartz seed crystal with a c-axis orientation and a length of 15 mm, with an angle of 90° to the surface of the glass melt, and slowly insert it into the glass melt to a depth of 1 / 2 of the length of the quartz seed crystal;

[0052] (3) Establishment of temperature gradient: By adjusting the heating system of the high-temperature furnace, establish a temperature gradient of 70 °C / cm along the c-axis direction of the quartz seed crystal in the glass melt, and the temperature at the end of the seed crystal inserted into the glass melt is 1500 °C, and the temperature at the other end is 1605 °C. Maintain this temperature gradient distribution throughout the glass melt to guide the crystal to grow along the c-axis direction of the seed crystal. The crystal growth rate is 0.5 mm / h, and the growth time is 12 h; when establishing the temperature gradient, by setting multiple thermocouples at different positions in the high-temperature furnace, monitor the temperature in real time and feedback to adjust the heating power to ensure the stability of the temperature gradient;

[0053] S3 Annealing: Cool the alkali-free glass substrate obtained in step S2 to 700 °C, hold for 4 h, and then cool to room temperature at a rate of 2 °C / h to eliminate the residual stress inside the alkali-free glass substrate, thus obtaining a zero-expansion glass substrate based on directional crystal growth.

[0054] Perform performance tests on the zero-expansion glass substrate based on directional crystal growth prepared in this example. The test results are as follows:

[0055]

[0056] Example 2

[0057] The zero-expansion glass substrate based on directional crystal growth in this example includes an alkali-free glass matrix and quartz crystals grown directionally along the c-axis, and the content of quartz crystals is 10 wt.%; among them, the alkali-free glass matrix includes the following components in mass percentages: SiO2: 60%, Al2O3: 18%, B2O3: 10%, MgO: 2%, CaO: 2%, TiO2: 1%, ZrO2: 1%, SnO2: 1.5%, Ga2O3: 3%, Tb4O7: 1.5%.

[0058] The preparation method of the zero-expansion glass substrate based on directional crystal growth in this example includes the following steps:

[0059] S1 Raw material preparation: Weigh each component with a purity ≥ 99.5 wt.%, and ball-mill and mix them until the particle size < 50 μm;

[0060] S2 Adding quartz crystals: Introduce quartz crystals into the alkali-free glass matrix by the floating zone method and control the growth of quartz crystals along the c-axis direction. Specifically, it includes the following steps:

[0061] 1) Preparation of the rod-shaped blank: Press the mixed components of the alkali-free glass matrix in step S1 into a rod-shaped blank with a diameter of 20 mm and a length of 200 mm; then pre-sinter it in a high-temperature furnace at a pre-sintering temperature of 1100 °C for 1.5 h to improve the strength and density of the blank;

[0062] 2) Installation of the seed crystal: Install a quartz seed crystal with a length of 15 mm oriented along the c-axis direction at one end of the floating zone furnace, axially align and coincide with the axis of one end of the rod-shaped blank, and control the axial deviation between the two within ±0.1 mm;

[0063] 3) Radio frequency heating and formation of the molten zone: Turn on the radio frequency heating system of the floating zone furnace, heat one end of the rod-shaped blank to make it locally molten to form a molten zone, and at the same time superimpose a mechanical oscillation of 0.3 Hz to promote the uniform distribution of solutes, and control the temperature of the molten zone to be 1700 °C and the length of the molten zone to be 8 mm;

[0064] 4) Establishment of temperature gradient: By adjusting the power distribution of the radio frequency heating system, a temperature gradient of 150 °C / cm is established in the molten zone along the direction consistent with the c-axis of the seed crystal. The temperature at the end of the molten zone close to the quartz seed crystal is 1650 °C, and the temperature at the far end is 1875 °C; the relative moving speed of the rod-shaped blank and the quartz seed crystal is 1 mm / h, and the growth time is 20 h; when establishing the temperature gradient, use the temperature feedback control system of the floating zone furnace to adjust the heating power according to the real-time temperature data to ensure the stability of the temperature gradient;

[0065] S3 Annealing: Cool the alkali-free glass substrate obtained in step S2 to 600 °C, hold for 6 h, and then cool to room temperature at a rate of 5 °C / h to eliminate the residual stress inside the alkali-free glass substrate, thus obtaining the zero-expansion glass substrate based on directional crystal growth.

[0066] Perform performance tests on the zero-expansion glass substrate based on directional crystal growth prepared in this example. The test results are as follows:

[0067]

[0068] Example 3

[0069] The zero-expansion glass substrate based on directional crystal growth in this example includes an alkali-free glass matrix and quartz crystals grown along the c-axis. The content of quartz crystals is 30 wt.%; the alkali-free glass matrix includes the following components in mass percentages: SiO2: 70%, Al2O3: 13.5%, B2O3: 6%, MgO: 2%, CaO: 2%, TiO2: 1%, ZrO2: 1%, SnO2: 1.5%, Ga2O3: 2%, Tb4O7: 1%.

[0070] The preparation method of the zero-expansion glass substrate based on directional crystal growth in this example includes the following steps:

[0071] S1 Raw material preparation: Weigh each component with a purity ≥ 99.5 wt.%, and ball-mill and mix them until the particle size < 50 μm;

[0072] S2 Adding quartz crystals: Introduce quartz crystals into the alkali-free glass matrix by the floating zone method and control the growth of quartz crystals along the c-axis direction. Specifically, it includes the following steps:

[0073] (1) Preparation of glass melt: Put the components of the alkali-free glass matrix mixed in step S1 into a high-temperature-resistant platinum crucible, place it in a high-temperature furnace, heat to 1500 °C, and hold for 4 h to melt and clarify the raw materials to form a glass melt; during the melting process, the melt can be appropriately stirred to promote the homogenization of the components;

[0074] (2) Introduction of seed crystal: Select a quartz seed crystal with a length of 12 mm and an orientation along the c-axis direction, with an angle of 85° to the surface of the glass melt, and slowly insert it into the glass melt. The insertion depth is 1 / 3 of the length of the quartz seed crystal.

[0075] (3) Establishment of temperature gradient: By adjusting the heating system of the high-temperature furnace, a temperature gradient of 100 °C / cm along the c-axis direction of the quartz seed crystal is established in the glass melt. The temperature at the end of the seed crystal inserted into the glass melt is 1450 °C, and the temperature at the other end is 1570 °C. The entire glass melt maintains this temperature gradient to guide the crystal growth along the c-axis direction of the seed crystal. The crystal growth rate is 0.1 mm / h, and the growth time is 12 h.

[0076] S3 Annealing: Cool the alkali-free glass substrate obtained in step S2 to 650 °C, hold for 2 h, and then cool to room temperature at a rate of 1 °C / h to eliminate the residual stress inside the alkali-free glass substrate, thus obtaining a zero-expansion glass substrate based on directional crystal growth.

[0077] Perform performance tests on the zero-expansion glass substrate based on directional crystal growth prepared in this example. The test results are as follows:

[0078]

[0079] Comparative Example 1

[0080] The difference from Example 1 is that the alkali-free glass matrix includes the following components by mass percentage: SiO2: 67%, Al2O3: 16.5%, B2O3: 8%, MgO: 2%, CaO: 2%, TiO2: 1%, ZrO2: 1%, SnO2: 1.5%, Tb4O7: 1%.

[0081] Perform performance tests on the glass substrate of Comparative Example 1. The test results are as follows:

[0082]

[0083] Since Ga2O3 was not added to the alkali-free glass matrix in Comparative Example 1, the interfacial energy increased, the crystal orientation degree decreased, and the c-axis negative expansion contribution was insufficient, resulting in a significant increase in the thermal expansion coefficient. At the same time, the disordered crystal growth introduced defects, resulting in a decrease in mechanical strength and light transmittance, and also affecting chemical stability.

[0084] Comparative Example 2

[0085] The difference from Example 1 is that the alkali-free glass matrix includes the following components by mass percentage: SiO2: 66%, Al2O3: 16.5%, B2O3: 8%, MgO: 2%, CaO: 2%, TiO2: 1%, ZrO2: 1%, SnO2: 1.5%, Ga2O3: 2%.

[0086] Performance tests were conducted on the glass substrate of Comparative Example 2, and the test results are as follows:

[0087]

[0088] In Comparative Example 2, Tb4O7 was not added, the energy distribution at the crystal growth interface was not effectively regulated, the orderliness of atomic arrangement in the c-axis direction decreased, the tendency of quartz crystal to grow directionally along the c-axis weakened, so that the negative thermal expansion property of the c-axis could not be fully exerted, resulting in an increase in the coefficient of thermal expansion. At the same time, the disorder of crystal growth increased, which affected the mechanical strength, light transmittance and chemical stability of the glass substrate to a certain extent.

[0089] Comparative Example 3

[0090] The difference from Example 1 is that the alkali-free glass matrix comprises the following components in mass percentages: SiO2: 60%, Na2O 5%, Al2O3: 16.5%, B2O3: 8%, MgO: 2%, CaO: 2%, TiO2: 1%, ZrO2: 1%, SnO2: 1.5%, Ga2O3: 2%, Tb4O7: 1%.

[0091] Performance tests were conducted on the glass substrate of Comparative Example 3, and the test results are as follows:

[0092]

[0093] Alkali metal oxides were added to the alkali-free glass matrix in Comparative Example 3, and Na + ion migration interfered with crystal growth, the degree of orientation decreased, and the coefficient of thermal expansion increased significantly; at the same time, alkali metals would also reduce the stability of the glass network, resulting in increased chemical erosion, and the electrical properties deteriorated due to ionic conduction.

[0094] Comparative Example 4

[0095] The difference from Example 1 is that steps (1)-(3) are not carried out, but the traditional crystal dispersion method is adopted. The specific operation process is as follows: after mixing the components of the alkali-free glass matrix evenly, during the formation of the glass melt, quartz crystal powder is directly added, no seed crystal is used, and no temperature gradient control is carried out. During the cooling process of the glass melt, the quartz crystals grow randomly.

[0096] Performance tests were conducted on the glass substrate of Comparative Example 4, and the test results are as follows:

[0097]

[0098] Comparative Example 4 used the traditional crystal dispersion method without seed crystal guidance, resulting in random crystal orientation. The c-axis negative thermal expansion effects offset each other, and the overall thermal expansion coefficient was close to that of traditional glass. The disordered distribution of crystals formed stress concentration points, significantly reducing the mechanical strength and light transmittance, proving that directional growth is the key to achieving zero expansion.

[0099] Comparative Example 5

[0100] The difference from Example 1 was that in step (2), after inserting the quartz seed crystal, the crystal growth rate was 0.5 mm / h and the growth time was 12 h; step (3) was not carried out.

[0101] The performance of the glass substrate of Comparative Example 5 was tested, and the test results were as follows:

[0102]

[0103] In Comparative Example 5, no temperature gradient was established during the seed crystal growth process, and the growth of quartz crystals lacked directional guidance. Although there was a seed crystal, the crystal growth direction still had a certain degree of randomness, resulting in the inability to fully utilize the c-axis negative thermal expansion characteristics and an increase in the thermal expansion coefficient. At the same time, the irregularity of crystal growth affected the microstructure of the glass substrate, leading to a decrease in mechanical strength and light transmittance. However, due to the lack of excessive impurities and defects introduced, the chemical stability and volume resistivity were relatively less affected.

[0104] Through the comparison of the above examples and comparative examples, it was verified that the directional growth technology, the alkali-free glass substrate formula, and the preparation method in the present invention successfully achieved directional growth control: by regulating the interfacial energy and atomic arrangement through Ga2O3 and Tb4O7, combined with seed crystals and temperature gradients, a c-axis orientation degree of ≥95% was achieved, ensuring the effective superposition of the negative thermal expansion effect. Advantages of the alkali-free glass substrate formula: avoiding the interference of alkali metal ions on crystal growth and electrical properties, and improving chemical stability and volume resistivity. Performance synergistic optimization: the directional arrangement of crystals not only offsets thermal expansion but also enhances mechanical strength by strengthening the phase interface bonding force, and the transparent matrix ensures high light transmittance, meeting the requirements of the optical and electronic fields and providing a reliable zero-expansion glass substrate solution for high-precision fields.

Claims

1. A zero-expansion glass substrate based on directional crystal growth, characterized in that, It includes an alkali-free glass matrix and quartz crystals grown along the c-axis, with the quartz crystal content being 10 - 30 wt.%. Among them, the alkali-free glass matrix includes the following components in mass percentages: SiO2: 60 - 70%, Al2O3: 10 - 18%, B2O3: 5 - 10%, MgO: 1 - 3%, CaO: 1 - 3%, TiO2: 0.5 - 2%, ZrO2: 0.5 - 2%, SnO2: 1 - 2%, Ga2O3: 1.5 - 3%, Tb4O7: 0.8 - 1.5%.

2. The preparation method of the zero-expansion glass substrate based on directional crystal growth according to claim 1, wherein, It includes the following steps: S1 Raw material preparation: Mix the components of the alkali-free glass matrix evenly; S2 Adding quartz crystals: Introduce quartz crystals into the alkali-free glass matrix by the melt texture method or the floating zone method and control the growth of quartz crystals along the c-axis direction; S3 Annealing: Anneal the alkali-free glass substrate obtained in step S2 to obtain a zero-expansion glass substrate based on directional crystal growth.

3. The preparation method of the zero-expansion glass substrate based on directional crystal growth according to claim 2, wherein, In step S1, the components are mixed by ball milling, and the particle size is <100 μm.

4. The preparation method of the zero-expansion glass substrate based on directional crystal growth according to claim 2, wherein, In step S2, the melt texture method includes the following steps: (1) Preparation of glass melt: Put the components of the mixed alkali-free glass matrix in step S1 into a crucible, place it in a high-temperature furnace, heat it to 1500 - 1700 °C, and keep it warm for 2 - 4 h to melt and clarify the raw materials to form a glass melt; (2) Introduction of seed crystal: Select a quartz seed crystal oriented along the c-axis direction, and insert it into the glass melt at an angle of 85 - 90° with the surface of the glass melt; (3) Establishment of temperature gradient: Establish a temperature gradient of 50 - 100 °C / cm along the c-axis direction of the quartz seed crystal in the glass melt, and the temperature at the end inserted into the glass melt is lower than that at the other end to guide the crystal to grow along the c-axis direction of the seed crystal.

5. The preparation method of a zero-expansion glass substrate based on directional crystal growth according to claim 4, characterized in that, In step (2), the depth of the quartz seed crystal inserted into the glass melt is 1 / 3 - 1 / 2 of the length of the quartz seed crystal.

6. The preparation method of the zero-expansion glass substrate based on directional crystal growth according to claim 4, characterized in that, In step (3), the crystal growth rate is 0.1 - 1 mm / h.

7. The preparation method of the zero-expansion glass substrate based on directional crystal growth according to claim 2, wherein, In step S2, the floating zone method includes the following steps: 1) Preparation of rod-shaped blank: Make the components of the mixed alkali-free glass matrix in step S1 into a rod-shaped blank with a diameter of 10 - 30 mm and a length of 100 - 300 mm; then pre-sinter it in a high-temperature furnace, and the pre-sintering temperature is 1000 - 1200 °C, and keep it warm for 1 - 2 h; 2) Installation of seed crystal: Install a quartz seed crystal oriented along the c-axis direction at one end of the floating zone furnace, axially align and coincide with the axis of one end of the rod-shaped blank; 3) Radio frequency heating and formation of melting zone: Heat one end of the rod-shaped blank to make it locally melt to form a melting zone, and at the same time superimpose a mechanical oscillation of 0.1 - 0.5 Hz to promote the uniform distribution of solute, control the temperature of the melting zone to be 1600 - 1800 °C, and the length of the melting zone is 5 - 10 mm; 4) Establishment of temperature gradient: Establish a temperature gradient of 100 - 200 °C / cm along the direction consistent with the c-axis of the seed crystal in the melting zone, and the temperature at the end of the melting zone close to the quartz seed crystal is lower than that at the end far from the quartz seed crystal.

8. The preparation method of the zero-expansion glass substrate based on directional crystal growth according to claim 7, characterized in that, In step 4), the relative movement speed of the rod-shaped blank and the quartz seed crystal is 0.5 - 2 mm / h.

9. The preparation method of the zero-expansion glass substrate based on directional crystal growth according to claim 2, wherein, In step S3, after crystal growth is completed, the alkali-free glass substrate is cooled to 600 - 700 °C, held at this temperature for 2 - 6 h, and then cooled to room temperature at a rate of 1 - 5 °C / h.